Editor - Parmaxi, Antigoni (My University, 2026)
Education for Sustainable Development (ESD) is the key driver for achieving Sustainable Development Goals (SDGs). Its deliberate, dynamic and interdisciplinary character in learning and teaching, underlies transformational learning environments and pedagogies that can support and empower learners, teachers, administrators, researchers to understand the systemic and global nature of sustainability issues and realise their role in pursuing change for creating more just, prosperous and sustainable societies. Digital Education represents a powerful tool for supporting ESD to meet current and future needs for integrating SDGs in all forms, levels of education and it responds to the changes, and challenges for creating transformative pedagogies, learning environments, contents and learning outcomes that can lead to a more resilient and sustainable world. Despite the interconnection and relationship that underlie Digital Education and ESD, however, we must not ignore the challenges that coexist for Digital Education per se and the impact that technology can have on learning for sustainable futures. The new strategic orientation for ESD2030 emphasizes the need to build and extend the way that digital education and technologies can be used for changing people’s behavior and frame of mind in relation to sustainability. Also, it addresses its role as a vehicle for developing inclusive educational opportunities that can accelerate initiatives and actions that can empower people, especially young, to acquire the knowledge, skills, values and attitudes needed for promoting sustainable development and achieving the 17 SDGs (2015; 2017). The goal of this special issue is to provide the opportunity to researchers, from various sciences (humanities, social sciences Technology, Human-Computer Interaction, Engineering, Social Computing etc), to share their ideas, practices, and research regarding the developments on the digital education and ESD and how they can contribute to the achievement of SDGs in Education. The special issue also aims to add to the discussion on how digital education and technologies can enhance ESD practices, learning environments, pedagogies and contents in all forms of education in order to mobilize people to take the appropriate actions that can lead to sustainability in all aspects of life. Finally, it aims to critically reflect on the challenges, risks and emergencies of digital education in ESD. This Research Topic encourages for cases, reviews and research articles to discuss the digital education developments, as well as challenges in the interdisciplinary light of ESD. The issue is open to submissions of original articles, subject to a rigorous peer review, covering the recent debate on the benefits and risks of digital education in reorienting education towards sustainability with an emphasis on learning environments and pedagogies (MOOCs, robotics, artificial intelligence, mixed reality etc), on teaching and learning SDGs by using digital education and technology, on the developments in ESD and Digital Education in national and regional level. We look forward to interdisciplinary contributions from the field of education, sustainability, social computing, technology, sciences etc. Keywords: emerging technologies, digital activism, sustainable development goals, techology-enhanced, education, sustainability, transformation, digitalization, technology